Drawing matters. Issue 1 (1st April 2022) - Riley, Howard; Darlington, Michelle
As the faculties of literacy and numeracy are universally recognized as worthy of pedagogical nurturing, so this article champions an older, graphic articulacy: visualcy. An articulacy with the language of drawing that distinguishes the visual arts from other disciplines. Its nurturing has been compromised by the shift away from teaching drawing in UK secondary schools and HE art schools, even before COVID. We argue that this shift is in part a consequence ‐ perhaps unintended ‐ of the neo-liberal values permeating the UK education sector. The article presents a critique of the those values seen as a significant obstacle to drawing's educational benefits, and offers an optimistic basis for its place in the curriculum.